2019
DOI: 10.1177/1524838019850623
|View full text |Cite
|
Sign up to set email alerts
|

Battered and Brain Injured: Traumatic Brain Injury Among Women Survivors of Intimate Partner Violence—A Scoping Review

Abstract: Objectives: The objective of this scoping review is to examine the extent, range, and nature of literature targeting health-care professionals on the prevalence and outcome of intimate partner violence (IPV)-related traumatic brain injury (TBI). The purpose is to gain an understanding of prevalence, investigate screening tool use, generate IPV/TBI-specific support recommendations, and identify suggestions for future research. Method: The review was guided by Arksey and O’Malley’s five stages for conducting a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 58 publications
3
78
0
Order By: Relevance
“…34 Females had a significantly higher odds of sustaining TBI through physical abuse, an important and actionable finding that parallels recent studies that have evaluated TBI in individuals who are survivors of intimate partner violence. 35 Our findings also highlight notable associations between the severity and timing of TBI with housing status. First, moderate or severe TBI was closely related to the initial loss of stable housing, which suggests that a considerable proportion of newly homeless and precariously housed individuals may be acutely experiencing sequelae related to TBI.…”
Section: Discussionsupporting
confidence: 55%
“…34 Females had a significantly higher odds of sustaining TBI through physical abuse, an important and actionable finding that parallels recent studies that have evaluated TBI in individuals who are survivors of intimate partner violence. 35 Our findings also highlight notable associations between the severity and timing of TBI with housing status. First, moderate or severe TBI was closely related to the initial loss of stable housing, which suggests that a considerable proportion of newly homeless and precariously housed individuals may be acutely experiencing sequelae related to TBI.…”
Section: Discussionsupporting
confidence: 55%
“…2 Whereas there are distinct bodies of literature examining both IPV and TBI, only a few studies directly address the correlation between them; a scoping review conducted by the authors (in press) identified 20 English language original research studies expressly considering the intersection. 15 Existing studies have identified a relationship between IPV/TBI and a range of biopsychosocial challenges faced by survivors, 3,7,16–18 and explored various health care contexts, 19–23 as well as survivor categories such as veterans, 24 ethnic groups, 25 and marginalized women. 26 Yet, although the identified studies focused on prevalence rates, identification and screening, and recommendations for health care professionals, none of them address the state of TBI knowledge among frontline workers, an area highlighted as being of key importance.…”
Section: Introductionmentioning
confidence: 99%
“…The ABI-participants in the latter study ( 8 ) were, however, slightly younger and with a lower IQ relative to our sample. It is important to consider that several factors might contribute to bias, and differences, in patient and informant ratings (e.g., cognitive deficits, severe emotional regulation dysfunction, self-awareness, social desirability bias, informant's burden, abuse, stress level, and/or personality) ( 30 33 ), suggesting that information should be gathered from multiple sources. Finally, the majority of the participants chose a spouse/partner as an informant, and the remaining informants were parents, siblings, friends, or adult children.…”
Section: Discussionmentioning
confidence: 99%